2009
DOI: 10.3855/jidc.411
|View full text |Cite
|
Sign up to set email alerts
|

Identification and genotyping of the etiological agent of tuberculous lymphadenitis in Ethiopia

Abstract: Background: In Ethiopia, little has been done to assess how Mycobacterium bovis has contributed to human tuberculosis, though the population routinely consumes unpasteurized milk and raw meat. The aim of this study was to determine the proportion of M. tuberculosis and M. bovis as etiological agents of tuberculous lymphadenitis (TBLN). Methods: Patients with lymphadenopathy (n = 171) were included in a cross-sectional study at Butajira Hospital, Southern Ethiopia. Lymph node biopsies were cultured. Patients' H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 23 publications
6
26
1
1
Order By: Relevance
“…This finding is compatible with previous studies in Ethiopia [3133]. However, M. bovis was isolated from the two TBLN cases even though cattle owned by these patients were none reactor for CIDT test.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is compatible with previous studies in Ethiopia [3133]. However, M. bovis was isolated from the two TBLN cases even though cattle owned by these patients were none reactor for CIDT test.…”
Section: Discussionsupporting
confidence: 92%
“…This has been also evident from earlier studies conducted in other regions of Ethiopia [25,26]. This study also evaluated the association of TB occurrence with different risk factors, such as age, sex, residence area, occupation, education, marital status, alcohol intake, tobacco or shisha use, previous TB contact history, stages of HIV or ART use and CD4 count; however, none of these factors significantly correlated with the occurrence of TB (p > 0.05).…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, this might indicate that the route of acquisition of lymph node TB is probably the same as pulmonary and can partly explain why Mycobacterium bovis was not detected. Other studies have reported a predominance of Mycobacterium tuberculosis in TB lymphadenitis in Ethiopia [15,16] although bovine transmission would be expected where raw milk is consumed.…”
Section: Discussionmentioning
confidence: 99%